2019
DOI: 10.18632/aging.102325
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TTN-AS1 regulates osteosarcoma cell apoptosis and drug resistance via the miR-134-5p/MBTD1 axis

Abstract: Aim: To explore the mechanism by which long non-coding RNA (lncRNA) TTN-AS1 regulates osteosarcoma cell apoptosis and drug resistance via the microRNA miR-134-5p/malignant brain tumour domain containing 1 (MBTD1) axis.Results: The lncRNA TTN-AS1 was highly expressed in osteosarcoma and was associated with poor prognosis. The lncRNA TTN-AS1 promoted cell viability and inhibited apoptosis. MiR-134-5p targeted MBTD1, which was regulated by lncRNA TTN-AS1. MBTD1 was highly expressed in osteosarcoma and was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 36 publications
5
100
0
Order By: Relevance
“…As radiotherapy is a very important treatment for esophageal cancer patients, radiotherapy resistance has been attracting more and more attention from clinicians and researchers in the field. Previous studies have found that radiotherapy can induce tumor cell apoptosis and that tumor sensitivity to radiotherapy is consistent with tumor cell sensitivity to apoptosis (Simpson & Scholefield, 2008;Tut et al, 2015 (Fu et al, 2019), we found here a potential similar molecular mechanism for TTN-AS1 to inhibit apoptosis. Recently, miR-134 has been identified as a potential cancer suppressor and identified as deregulated in various types of human cancer, such as lung cancer, glioblastoma, breast cancer, colorectal cancer, and others (Pan et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As radiotherapy is a very important treatment for esophageal cancer patients, radiotherapy resistance has been attracting more and more attention from clinicians and researchers in the field. Previous studies have found that radiotherapy can induce tumor cell apoptosis and that tumor sensitivity to radiotherapy is consistent with tumor cell sensitivity to apoptosis (Simpson & Scholefield, 2008;Tut et al, 2015 (Fu et al, 2019), we found here a potential similar molecular mechanism for TTN-AS1 to inhibit apoptosis. Recently, miR-134 has been identified as a potential cancer suppressor and identified as deregulated in various types of human cancer, such as lung cancer, glioblastoma, breast cancer, colorectal cancer, and others (Pan et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…***p < .001 versus control group, ### p < .001 versus miR-134-5p-NC group. p Value is calculated by one-way ANOVA followed by Duncan's test (Fu et al, 2019). Moreover, our results provide clear evidence that TTN-AS1 increases X-ray resistance of human large intestine cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 65%
“…Increasing evidence has indicated that lncR-NAs play an important role in various human diseases, especially in malignant tumors [21][22][23][24]. Antisense long non-coding RNAs, such as TTN-AS1, IDH1-AS1 and AFAP-AS1, have been reported in tumors and closely related to the prognosis, development, invasion and metastasis of tumors [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences have showed that aberrant expression of lncRNA could drive tumor phenotypes, including initiation, invasion, and metastasis, via interacting with other cellular macromolecules [9]. More recently, emerging lncRNAs have been identified and characterized as crucial factors in tumorigenesis, with certain reports highlighting them as biomarkers and targets in various cancers, such as breast cancer antiestrogen resistance 4 (BCAR4) [10], small nucleolar RNA host gene 16 (SNHG16) [11], and TTN antisense RNA 1 (TTN-AS1) [12].…”
Section: Introductionmentioning
confidence: 99%